Functional outcomes and activity levels in patients after internal hemipelvectomy for primary sarcoma involving the bony pelvis - Lehner, Burkhard; Bollmann, Jakob; Geisbüsch, Andreas; Beckmann, Nicholas A. (Diagnostics, 2025)
Background: Internal hemipelvectomies are rare procedures for primary musculoskeletal sarcomas of the bony pelvis. There is a sparse amount of data on functional outcomes and activity levels in postoperative patients. The aim of this study was to investigate functional outcomes, including sport activity levels, and the impact of tumor grade, resection margins, adjuvant therapies, pelvic reconstruction, and patient age at the time of surgery. Methods: Patients who underwent internal hemipelvectomy at our clinic between 1995 and 2019, with a minimum follow-up of 12 months, were assessed using the Musculoskeletal Tumor Society Score (MSTS), the Toronto Extremity Salvage Score (TESS), the Oxford Hip Score (OHS), and the University of Los Angeles Activity Scale (UCLA AS). Results: Our cross-sectional study included 29 patients (14 male, 15 female; 15 with chondrosarcoma, 8 with Ewing’s sarcoma, 2 with osteosarcoma, 2 with chordoma, and 2 with other sarcomas) with a median follow-up of 8.7 years (range: 12 months to 25.4 years; interquartile range (IQR): 13.1 years). The median MSTS was 16 (range: 1-30; IQR: 9), median TESS was 75.8% (range: 12.9-100%; IQR: 31.7%), median OHS was 35 (range: 10-48; IQR: 16), and median UCLA AS was 5 (range: 1-9; IQR: 3). Tumor grade, resection margins, chemotherapy, radiation therapy, and pelvic reconstruction had no significant effect on functional outcomes. Patient age at the time of surgery had a statistically significant effect on all measured outcome parameters, although all parameters exhibited a wide range and large IQR, likely reflecting the small, heterogeneous patient cohort. Conclusions: Surviving patients who underwent internal hemipelvectomy for primary musculoskeletal sarcomas of the pelvic bone demonstrated overall moderate to good functional outcomes and moderate sport activity levels.
Gesehen am 27.10.2025